ABDUL-HAMID (IMAM) GHAZALI: IHYA ULUM ID-DIN (REVIVAL OF RELIGIOUS THOUGHT), VOL. 4. DARUL-ISHAAT URDU BAZAR KARACHI-PAKISTAN, 1993 - Choudry, Masud (University of Darussalam Gontor Press, 2024)
This book provides a review of the book “Ihya Ulum Id-Din (Revival ofReligious Thought Volume 04)” the work of Islamic scholar Imam Abdul HamidAl-Ghazali (Imam Ghazali Translated by Fazlul Karim. Darul Ishaat, Urdu Bazar,Karachi, Pakistan, 1993. This is an original contribution, explained in informativecontent and written in clear language that is accessible to knowledgeable readers